CONCEPTUAL METAPHOR IN THE POETRY COLLECTION LOVE LETTERS FOR THE FUTURE YOU BY ADI K : COGNITIVE SEMANTICS STUDY - Al Qorni, Wais; Tarihoran, Rezky Khoirina (PHILOLOGY Journal of English Language and Literature, 2024)
This research aims to find out the types of conceptual metaphors and then describe the meanings of these types of conceptual metaphors. This research uses the theory of Conceptual Metaphor from Lakoff and Jhonson (2003) followed by the study of Cognitive Semantics. This research uses qualitative research methods. The data used in this research is a poetry collection book entitled Love Letters for the Future You by Adi K. The results of this study show that there are 3 types of Conceptual Metaphors, namely Structural Metaphors, Orientational Metaphors, and Ontological Metaphors based on the theory of Lakoff and Jhonson (2003). This study found 4 data of Conceptual Metaphor of Structural Metaphor type. In addition, this study found 3 data of Conceptual Metaphor from the type of Orientational Metaphor. And finally, this study found 3 data of Conceptual Metaphor of Ontological Metaphor type.